A missed orthopaedic injury following a seizure: a case report - O'Connor-Read, Laurence (BioMed Central, 2007)
Numerous orthopaedic injuries can follow a seizure and are often diagnosed late. This is the first documented case of a missed bilateral anterior shoulder dislocation following a seizure. The possible reasons for the greater incidence of posterior dislocations are examined and why bilateral anterior dislocations following a seizure are so rare. The article discusses the reasons for the delay and highlights potential pitfalls and learning points for junior emergency department doctors.